Prediction of post-storage quality in canning apricots and peaches using near infrared spectroscopy (NIRS) and chemometrics - Myburgh, Lindie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2003.